1983
DOI: 10.1159/000149344
|View full text |Cite
|
Sign up to set email alerts
|

An Arenavirus Isolated from Wild-Caught Rodents (<i>Praomys</i> Species) in the Central African Republic

Abstract: We isolated nine arenavirus strains from blood and/or tissues of Praomys sp. rodents wild-caught in derived savannah and forest gallery areas of the Central African Republic (CAR). Convalescent serum from either humans or animals infected by Lassa, Mozambique, or lymphocytic choriomeningitis virus cross-reacted with the strains from the CAR. However, monoclonal antibodies to these three viruses gave a profile against the CAR strains suggesting major antigenic differences between each of them and the CAR virus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 7 publications
0
27
0
1
Order By: Relevance
“…The pathogenicity of Morogoro virus for humans is not known, though its phylogenetic clustering with African arenaviruses that are not linked with human disease ( 4 – 6 ) and the absence of hemorrhagic fever in the area suggest that it does not cause severe disease. Hospital-based investigations are required to estimate the public health relevance of this virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenicity of Morogoro virus for humans is not known, though its phylogenetic clustering with African arenaviruses that are not linked with human disease ( 4 – 6 ) and the absence of hemorrhagic fever in the area suggest that it does not cause severe disease. Hospital-based investigations are required to estimate the public health relevance of this virus.…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples were tested by indirect immunofluorescent antibody (IFA) assay ( 8 ). Lassa virus was used as antigen due to its cross-reactivity with immune sera from animals infected with other arenaviruses ( 4 , 6 ). Clusters of seropositivity were found in Arvicanthis spp.…”
Section: The Studymentioning
confidence: 99%
“…The prototype strains of MAC (Carvallo), JUN virus (XJ), LAS (LP), and MOP (AN20410) viruses were obtained from the virus collection of the Special Pathogens Branch, CDC. The prototype strain of MOB virus (3076) was unavailable for this study so two other strains (3051, 3099) which were reported with the prototype in the initial study of MOB virus (Gonzalez et al, 1983) were analyzed instead. The prototype strain of Ippy virus (Dak An B 188 d) was obtained from Dr. Robert Shope, University of Texas Medical Branch at Galveston, Galveston, Texas.…”
Section: Virus Strainsmentioning
confidence: 99%
“…The NW arenaviruses are associated with rodents in the subfamily Sigmodontinae of the family Cricetidae, whereas the OW arenaviruses are associated with rodents in the subfamily Murinae of the family Muridae. LASV and Mopeia virus (MOPV; Wulff et al, 1977) are hosted by members of the genus Mastomys, Mobala virus (MOBV; Gonzalez et al, 1983) by Praomys spp., Ippy virus (IPPYV; Meunier et al, 1985;Swanepoel et al, 1985) by Arvicanthis spp., and lymphocytic choriomeningitis virus (LCMV; Peters, 2006) by the ubiquitous Mus musculus.…”
Section: Introductionmentioning
confidence: 99%